Analisis Kinerja Bank Syariah di Indonesia Berbasis Maqashid Sharia Index - Prima Dwi Priyatno; Ade Nur Rohim; Lili Puspita Sari (ITB AAS INDONESIA Surakarta, 2022)
Development of the banking industry that continues to increase from year to year, there must be a balance in terms of performance assessment, where the performance measurement of Islamic banking does not only look at the profit side, but Islamic banking as a sharia business entity needs to consider aspects of benefit and conformity with sharia maqashid. Performance measurement with the maqashid sharia index approach has three objective indicators. Indicators of Education (Tahdzib Al-Fard), Establishing Justice (Al-'Adl), and Public Interest (Al-Mashlahah). From the data collected, the results of the analysis of performance measurement based on Islamic maqashid for the twelve Islamic Commercial Banks, Panin Dubai Syariah Bank (PDS) have the highest performance value with an index value of 0.42563. The level of performance index based on sharia maqashid shows a gradual level, the higher the level of value generated, it can be said that the better in achieving the goals and principles of sharia, and vice versa, the lower the index value produced, the lower the performance in creating the benefits of shariah goals. want to achieve.